2014
DOI: 10.1614/wt-d-13-00099.1
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Programs for Controlling Glyphosate-Resistant Johnsongrass (Sorghum halepense) in Glufosinate-Resistant Soybean

Abstract: Three field experiments were conducted in 2010 and 2012 in a soybean production field near West Memphis, AR, containing glyphosate-resistant johnsongrass. The goal of this research was to develop effective herbicide programs for glyphosate-resistant johnsongrass in glufosinate-resistant soybean. Control of the resistant johnsongrass was greater with glufosinate at 590 and 740 g ai ha−1than at 450 g ha−1. Sequential glufosinate applications were more effective than a single application, irrespective of rate. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…Use of commercially available PRE herbicides, particularly for soybean and maize, with different modes of actions (e.g., s-metolachlor, pendimethalin, flufenacet, and clomazone) were reported to be effective in controlling S. halepense seedlings, not regrowth from rhizomes (Scarabel et al 2014). Since their introduction in the 1980s, POST herbicides, mainly acetyl-coenzyme-A carboxylase (ACCase) and acetolactate synthase (ALS)-inhibitors, have showed a high efficacy against both the seedlings and rhizomes of S. halepense (Johnson et al 2014b;Johnson and Norsworthy 2014;Scarabel et al 2014). Among these herbicide groups, sulfonylureas, aryloxyphenoxypropionates (FOPs), and cyclohexanediones (DIMs) are widely applied for control of S. halepense in maize, soybean, cotton, and other dicotyledonous crops (Bridges and Chandler 1987b;Corkern et al 1998;Sarpe et al 2000;Smeda et al 2000;Kaloumenos and Eleftherohorinos 2009).…”
Section: Herbicide-susceptible Biotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of commercially available PRE herbicides, particularly for soybean and maize, with different modes of actions (e.g., s-metolachlor, pendimethalin, flufenacet, and clomazone) were reported to be effective in controlling S. halepense seedlings, not regrowth from rhizomes (Scarabel et al 2014). Since their introduction in the 1980s, POST herbicides, mainly acetyl-coenzyme-A carboxylase (ACCase) and acetolactate synthase (ALS)-inhibitors, have showed a high efficacy against both the seedlings and rhizomes of S. halepense (Johnson et al 2014b;Johnson and Norsworthy 2014;Scarabel et al 2014). Among these herbicide groups, sulfonylureas, aryloxyphenoxypropionates (FOPs), and cyclohexanediones (DIMs) are widely applied for control of S. halepense in maize, soybean, cotton, and other dicotyledonous crops (Bridges and Chandler 1987b;Corkern et al 1998;Sarpe et al 2000;Smeda et al 2000;Kaloumenos and Eleftherohorinos 2009).…”
Section: Herbicide-susceptible Biotypesmentioning
confidence: 99%
“…The introduction of glufosinate-tolerant crops has provided farmers with alternatives for the control of this weed without any crop injury e.g. glufosinate, s-metolachlor, pendimethalin, flufenacet, and clomazone (Johnson and Norsworthy 2014;Scarabel et al 2014;Johnson et al 2014b;Landry et al 2016). Sarpe et al (2000) Failures in weed control are usually associated with a mismatch between the weed population, herbicide application time, and herbicide sub-doses (Uremis et al 2009).…”
Section: Herbicide-resistant Biotypesmentioning
confidence: 99%
“…Conversely, Johnson et al [41] observed no differences in glufosinate-resistant soybean yield following herbicide programs for johnsongrass control (2,690 to 3,160 kg ha −1 ); however, differences might have been observed if their studies had not been sprayed with clethodim 10 WAE.…”
Section: Soybean Yieldmentioning
confidence: 88%
“…This observation may be due to increased johnsongrass leaf number (5 leaves versus 7 leaves) providing greater interception of glufosinate when applied POST3. Johnson et al [41], Wiesbrook et al [50], and Prostko et al [51] suggested that sequential applications of herbicides are more effective at controlling weeds.…”
Section: Glyphosate-resistant Rhizomatous Johnsongrass Controlmentioning
confidence: 99%
See 1 more Smart Citation